2013
DOI: 10.1007/s00167-013-2561-5
|View full text |Cite
|
Sign up to set email alerts
|

Tibial rotational osteotomy and distal tuberosity transfer for patella subluxation secondary to excessive external tibial torsion: surgical technique and clinical outcome

Abstract: Case series, Level IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
68
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(76 citation statements)
references
References 56 publications
2
68
0
6
Order By: Relevance
“…25 The cut-off point of 20 mm above which tibial tubercle osteotomy is indicated has been well accepted by most orthopaedic surgeons. [26][27][28][29][30] One study has shown that 18% of recurrent patellar dislocators had TT-TG distances of >20 mm. 31 For patients with significant trochlear dysplasia, trochleoplasty procedures have been advocated.…”
Section: Discussionmentioning
confidence: 99%
“…25 The cut-off point of 20 mm above which tibial tubercle osteotomy is indicated has been well accepted by most orthopaedic surgeons. [26][27][28][29][30] One study has shown that 18% of recurrent patellar dislocators had TT-TG distances of >20 mm. 31 For patients with significant trochlear dysplasia, trochleoplasty procedures have been advocated.…”
Section: Discussionmentioning
confidence: 99%
“…Другие же считают, что эти процессы могут возникать только при сгибании >80° и классических приседаниях [35,36]. Боль-шинство учёных склоняются к тому, что нагрузочный стресс-пик в структуре над-коленника максимально нарастает при сги-бании в КС на 90° [31].…”
Section: Etiopathogenic Bases For Patellofemoral Arthritis Developmentunclassified
“…Это происходит за счёт механизма его деформации: верх-ний полюс компрессируется в медиальном направлении. Примечательно, что превен-тивно выполненное оперативное вмеша-тельство в виде деротационной остеотомии большеберцовой кости позволяет предот-вратить развитие ПФА [31,36].…”
Section: Etiopathogenic Bases For Patellofemoral Arthritis Developmentunclassified
“…5) Torsionsosteotomien haben einen signifikanten und effektiven Einfluss auf das Patellatracking -insbesondere in strecknahen Beugewinkeln [21]. Dementsprechend werden in der Literatur hohe Erfolgsraten mit Torsionsosteotomien bei entsprechenden patellaren Problematiken angegeben [5,9,10,24].…”
Section: Torsionsabweichungenunclassified